Respuesta :
Hello! And thank you for your question!
First move all the terms to one side:
x^2−4x−9−29=0
Then simplify x^2−4x−9−29:
x^2−4x−38=0
Then use the quadratic formula:
x = 4 + 2√42 over 2 , 4 - 2√42 over 2
Finally simplify:
x = 2 + √42, 2 - √42
Final Answer:
x = 2 + √42, 2 - √42
First move all the terms to one side:
x^2−4x−9−29=0
Then simplify x^2−4x−9−29:
x^2−4x−38=0
Then use the quadratic formula:
x = 4 + 2√42 over 2 , 4 - 2√42 over 2
Finally simplify:
x = 2 + √42, 2 - √42
Final Answer:
x = 2 + √42, 2 - √42
Hello there!
Check the picture for the answer.
Let me know if you have any questions.
Best of luck with your studies!
Thanks!
Check the picture for the answer.
Let me know if you have any questions.
Best of luck with your studies!
Thanks!
![Ver imagen garydesir1](https://us-static.z-dn.net/files/d9f/a719a5719e68afa968609090e119444f.png)